Assessment of lipid-lowering therapy prescribing among patients with type 2 Diabetes Mellitus in Malaysian primary care settings - Elnaem, Mohamed Hassan; Nik Mohamed, Mohamad Haniki (International Society for Pharmacoeconomics and Outcomes Research (ISPOR), 2017)
Dyslipidemia is a major contributor to the evolution of cardiovascular disease (CVD) among patients with type 2 diabetes mellitus (T2DM). There is a guideline recommendation to offer statin therapy to all T2DM patients between 40 to 75 years old for either primary or secondary CVD prophylaxis. Nevertheless, the suboptimal management of diabetic dyslipidemia in the Malaysian primary care settings has been reported. This study aimed to describe the statin therapy prescribing pattern among patients with T2DM, evaluate the appropriateness of statin therapy prescribing, and assess the level of achievement of the primary target (LDL-C) for diabetic dyslipidemia treatment.